2022
DOI: 10.3389/fmicb.2022.987613
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characterization of antimicrobial resistance profiles in Salmonella isolated from waterfowl in 2002–2005 and 2018–2020 in Sichuan, China

Abstract: Salmonella enterica is a widespread foodborne pathogen with concerning antimicrobial resistance (AMR). Waterfowl are a major source of Salmonella transmission, but there are few systematic studies on Salmonella prevalence in waterfowl species. In this study, 126 Salmonella isolates (65 collected in 2018–2020 and 61 collected in 2002–2005) were obtained from waterfowl samples in Sichuan, China. Their serotypes, pulsed-field gel electrophoresis (PFGE) types, and phenotypic and genotypic AMR profiles were systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…In another study, 126 Salmonella isolates dispersed among seven serotypes were shown to be multidrug-resistant, with high rates of AMR to lincomycin (100%), rifampicin (100%), sulfadiazine (93.7%), erythromycin (89.7%), ciprofloxacin (81.0%), and gentamicin (75.4%). (Guan et al 2022 )…”
Section: Discussionmentioning
confidence: 98%
“…In another study, 126 Salmonella isolates dispersed among seven serotypes were shown to be multidrug-resistant, with high rates of AMR to lincomycin (100%), rifampicin (100%), sulfadiazine (93.7%), erythromycin (89.7%), ciprofloxacin (81.0%), and gentamicin (75.4%). (Guan et al 2022 )…”
Section: Discussionmentioning
confidence: 98%